ANALISIS STABILITAS LERENG JALAN SEGMEN 01 PEMBANGUNAN RUAS JALAN TAWANG-NGALANG, NGLANGGERAN, KABUPATEN GUNUNGKIDUL, PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Veno Sholitha; Anggi Hermawan; Novandri Kusuma Wardana (ReTII, 2022)
Geographical conditions in Gunungkidul are one of the mountainous physiographic sub-zones which are dominated by hills and there are geological formations so that they are relatively sensitive to landslides. To prevent landslides, it’s necessary to analyze the stability of slopes at location. This study aims to analyze the safety factor and the probability of slope failure in the original condition in the construction of the 01 Tawang-Ngalang road segment, Nglanggeran, Gunungkidul regency Special Region of Yogyakarta. The analysis of this study uses a boundary with probability analysis using slide software V7.0 by reocscience with two-dimensional modeling. This study uses primary and secondary data for analysis and modeling on 3 road slopes with different geometries, material properties obtained from the results of physical and mechanical laboratory tests. Based on the slope analysis on 3 slope models, it shows a safety value of 0.651 – 1.172 with a failure probability of 49.612 – 99.615% using the Janbu and Spencer methods. beside the research location is a discontinuous area that is relatively sensitive to landslides. Therefore, as a recommendation, sortcreate reinforcement and ground nailing are installed in the slope geometry field.